ITER-like antenna for JET first results of the advanced matching control algorithms - Durodié, F.; Dumortier, P.; Blackman, T.; Wooldridge, E.; Lerche, E.; Helou, W.; Goulding, R.H.; Kaufman, M.; Křivská, A.; Van Eester, D.; Graham, M. (Fusion engineering and design, 2017)
•The various matching feedback loops of the ITER-like antenna (ILA) for JET are described.•The performance of these feedback loops is illustrated.•The model simulation of the ILA and the experimental results are compared. The ITER-Like Antenna (ILA) for JET is a 2 toroidal by 2 poloidal array of Resonant Double Loops (RDL). It features in-vessel matching capacitors feeding RF current straps in Conjugate-T (CT) manner, a low impedance quarter-wave impedance transformer and a service stub allowing hydraulic actuator and water cooling services to reach the aforementioned capacitors. A Second Stage Matching (SSM) trombone and stub circuit allows to match the chosen CT working impedance to 30Ω. Toroidally adjacent RDLs are fed from a 3dB hybrid splitter. It is worth mentioning that while the in-vessel matching approach was not kept for the ICRF antenna for ITER, the other aspects of the design for ITER such as the use of short straps, the validation of the TOPICA coupling code as well as operation at >40kV and >5MW/m2 were confirmed by the ILA. The assessment of the ILA results (2008–9) identified that achieving routine full array operation required a better understanding of the RF circuit, tighter calibrations of RF measurements and last but not least a feedback control algorithm for the SSM. The matching and phasing of the array is controlled by 22 feedback loops actuating the 8 matching capacitors, the 4 second stage trombones and 4 stubs, the 4 Main Transmission Line (MTL) phase shifters and the 4 phases with respect to a reference of the generators feeding the upper and lower half array through 3dB hybrid combiner-splitters. The circuit was extensively simulated allowing the development of an algorithm to drives the SSM circuit components, trombone and stub, to optimal locations with respect to the measured remaining VSWR excursions due to ELMs. The paper focusses on the new additional matching algorithms and assesses their performance.